Benediction - Haruf, Kent (Alfred A. Knopf, 2013)
A terminally ill cancer patient is attended throughout his final days by his wife and daughter while the trio contemplates their relationships with an estranged son, a situation that stirs up painful memories for a new next-door neighbor who has recently lost her mother.